Associations between recollected rates of Category D fruit machine use as a child and adult gambling in a young adult sample - Philip Newall (Scientific Reports, 2023)
Abstract There have been recent restrictions to the range of gambling products made available to UK children, with the industry association Bacta introducing a minimum age of 18 for Category D fruit machines, which can otherwise be legally used by children. Any potential government action on Category D fruit machines may want to consider limitations in the current evidence base. The present study addressed this issue, by conceptually replicating previous results associating recollected usage of Category D fruit machine usage as a child and adult gambling. Compared to previous studies, the present study used a younger adult sample, and also tested for potential moderation by subjective confidence. Three out of four main tested associations were significant and in the hypothesised direction, and a lack of significance on interaction terms yielded no evidence of potential moderation by subjective confidence. The present study therefore added to the limited evidence base on potential risks of legal Category D fruit machine usage as a child.